2004
DOI: 10.1007/s10522-004-3200-9
|View full text |Cite
|
Sign up to set email alerts
|

Male Drosophila melanogaster flies exposed to hypergravity at young age are protected against a non-lethal heat shock at middle age but not against behavioral impairments due to this shock

Abstract: Previous studies have shown that exposing flies to hypergravity (3 or 5 g) for two weeks at young age slightly increases longevity of male flies and survival time at 37 degrees C of both sexes, and delays an age-linked behavioral change. The present experiments tested whether hypergravity could also protect flies from a non-lethal 37 degrees C heat shock applied at young, middle or old age (2, 4 or 6 weeks of age). Various durations of exposure at 37 degrees C had similar deleterious effects on climbing activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…However, it is possible that conditioning hormesis in the pupal stage might prime future responses to stressors at a later age, providing additional defense (Le Bourg et al, 2004;Le Bourg, 2005). Our results do support the idea that endogenous antioxidant enzymes can play crucial roles in sexual selection in the face of oxidative stress.…”
Section: Discussionsupporting
confidence: 74%
“…However, it is possible that conditioning hormesis in the pupal stage might prime future responses to stressors at a later age, providing additional defense (Le Bourg et al, 2004;Le Bourg, 2005). Our results do support the idea that endogenous antioxidant enzymes can play crucial roles in sexual selection in the face of oxidative stress.…”
Section: Discussionsupporting
confidence: 74%
“…Studies on fruit flies show that hormetic effects are often larger in males than females (Salmon et al, 2001;Le Bourg et al, 2004;Le Bourg, 2005;Sørensen et al, 2007). They also show that stimulatory effects that can emerge for traits like longevity may be associated with detrimental effects for other traits, such as locomotor activity or learning (Le Bourg et al, 2004). Therefore, the depletion of thiols in females not exposed to heat stress or exposed to high stress when juvenile and then exposed to high stress at adulthood could have been traded off against other traits, whose maintenance could have been prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…These kinds of non-linear dose-response relationships are referred to as hormetic responses (Southam and Ehrlich, 1943) and have been described across a wide range of organisms (from bacteria to vertebrates), in response to exposure to at least 1000 different chemical and environmental stressors (Mattson and Calabrese, 2010). Although studies show that hormetic effects can emerge at any time throughout the individual's life (Mattson and Calabrese, 2010), they also suggest that such effects might be stronger when animals are exposed to mild stressors in early life (Bartling et al, 2003;Honma et al, 2003;Le Bourg et al, 2004). Understanding these processes may therefore be very important in determining how the early environment can help shape a phenotype adapted to the conditions the organism is most likely to experience in its adult environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to know whether a mild stress could also protect against deleterious but non-lethal stresses because animals are often subjected to non-lethal stresses, such as a sudden temperature rise. A previous article (Le Bourg et al 2004) has shown that 4-week-old male flies living in HG at young age lived slightly longer (+15%) after a single deleterious non-lethal heat shock (60 min or 90 min at 37 • C) than flies that always lived at 1g, but this positive effect of hypergravity was not observed in females or in older males.…”
Section: Introductionmentioning
confidence: 91%